Copper‐Promoted Tandem Three‐Component Access to Quinazolin‐4(H)‐imines and Benzimidazo[1, 2‐c]quinazolines. Issue 19 (13th August 2019) - Rodrigues, Romain; Tran, Lam Quang; Darses, Benjamin; Dauban, Philippe; Neuville, Luc
Abstract: A copper‐catalyzed three‐component assembly of cyanamides, 2‐cyanoarylboronic acids and amines has been developed, providing functionalized quinazolin‐4( H )‐imines. Subsequent access to benzimidazo[1, 2‐ c ]quinazolines is achieved building again on copper‐catalysis. One pot hydrolysis of quinazolin‐4( H )‐imines to quinazolin‐4(3 H )‐ones is also described. Guanidine formation, cyclization and intramolecular C−H bond amination are key features of the process fully mediated by copper. Abstract :